3-(Substituted Aryl)-1-benzofuranyl-2-propenones: Antimicrobial Properties of Some Chalcones-Type Compounds and their 2-Pyrazoline Derivatives. Issue 4 (2011) - Coşkun, Demet; Ahmedzade, Misir; Kirbağ, Sevda
Abstract : 2-Acetylbenzofuran on condensation with furan-2-carboxaldehyde and pyrrole-2-carboxaldehyde in methanolic KOH solution yielded the corresponding benzofuran chalcones. These two compounds and nine benzofuran chalcones were synthesized before, were further reacted with hydrazine hydrate in ethanol which led to the formation of 2-pyrazoline derivatives. All the synthesized compounds were characterized by elemental analysis, melting point determination, infrared spectroscopy and nuclear magnetic resonance spectroscopy. Nine chalcone-type compounds and eleven 2-pyrazolines were evaluated for their biological activities against the six bacteria and the three yeast and it was seen that thirteen compounds showed activity. Four of them are chalcone-type compounds showed more or less activity.